2019
DOI: 10.1002/aqc.3256
|View full text |Cite
|
Sign up to set email alerts
|

Listing may not achieve conservation: A call for proactive approaches to threatened species management

Abstract: Species listing and subsequent conservation efforts are dependent on a number of political, social, and scientific factors, often to the disadvantage of uncharismatic taxa, such as small, cryptic, and rare species, and those that lack commercial value. This case study examined the listing, impact assessment and conservation process of the critically endangered marine seaweed Nereia lophocladia (Nereia hereafter), which is a small and sporadically occurring species. Nereia was initially listed as vulnerable, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…However, non‐detection at a particular site does not necessarily imply absence due to Nereia 's alternation of generations life history and patchiness (for details, see Mamo et al. 2019). Geographic range size mediates a species' extinction risk, with a more extensive range reducing the likelihood of stochastic or direct pressures affecting all individuals (Gaston and Fuller 2009, Wootton and Pfister 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, non‐detection at a particular site does not necessarily imply absence due to Nereia 's alternation of generations life history and patchiness (for details, see Mamo et al. 2019). Geographic range size mediates a species' extinction risk, with a more extensive range reducing the likelihood of stochastic or direct pressures affecting all individuals (Gaston and Fuller 2009, Wootton and Pfister 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary survey results suggested that Nereia may be distributed further afield than previously thought (Kelaher and Mamo 2018, Mamo et al. 2019), with significant implications for the conservation of this critically endangered species. Here, we combine field surveys to assess Nereia 's wider distribution, with the characterization of genetic diversity, population structure, and candidate loci under putative selection.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Over recent decades, there has been increasing recognition of the importance of enhancing the priority given to conservation of places that have special importance for biodiversity (Lopoukhine and Ferreira de Souza Dias, 2012;Ovando et al, 2021). Various types of biodiversity features may contribute to an area's prioritization for enhanced risk aversion in management, including the presence of rare or vulnerable species (Walsh et al, 2013, Mamo et al, 2020, exceptional structural complexity and/or diversity of habitat features (Airoldi et al, 2008;Lipcius et al, 2019), critical functional significance such as the role of the areas as a migration corridor (Boulton et al, 2016;Lederhouse and Link, 2016), or simply by being in a comparatively undisturbed state (Bryan et al, 2011;Bax et al, 2016). Particular sites may be proposed as a priority for enhanced risk aversion due to even a single one of these types of features, but the features also may occur in a variety of combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Endangered species (e.g., listed under the Endangered Species Act; ESA), often tend to be obscure and insufficiently studied both in terms of their distribution or roles within ecosystems and ecosystem components (Cooke et al, 2012). Many of these species get listed in a reactionary approach on a regional level after often irreversible impacts have been done or cascading ecosystem effects have been set in motion (Bush et al, 2014; Mamo et al, 2019). Consequently, an overuse of biodiversity as a conservation priority indicator could potentially inadequately cover low diversity but high‐risk and high‐pressure regions, as biodiversity does not necessarily coincide with at‐risk species, or species with unique life history or distribution patterns (Bush et al, 2014; Mamo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%